Clinical Pharmacology Review of Plasma‐derived and Recombinant Protein Products: CBER Experience and Perspectives on Model‐Informed Drug Development. Issue 4 (26th May 2019) - Tegenge, Million A.; Mahmood, Iftekhar; Forshee, Richard
Abstract: Introduction: Clinical pharmacology studies are one of the major types of regulatory data submitted for review of therapeutic proteins regulated by the Center for Biologics Evaluation and Research (CBER). Aim: The primary objective of the current study is to provide an overview of the role of clinical pharmacology including pharmacokinetics (PK), pharmacodynamics (PD) and exposure‐response analysis at CBER. Furthermore, we aim to provide a baseline estimate for the use of quantitative clinical pharmacology studies prior to implementation of FDA's model‐informed drug development (MIDD) pilot programme. Methods: We survey original Biologics License Applications (BLAs) for plasma‐derived and related recombinant therapeutic protein products approved by CBER/FDA (2008‐2017). Results: There were 37 original BLAs that met our inclusion criteria, and 34 of these products (92%) contained human PK data as part of the biological licensing. The products were broadly classified as coagulation factors (54%), IgG and related proteins (24%), and other therapeutic proteins (22%). Coagulation factor VIII and IX products constitute 32% of the BLAs and indicated for treatment of haemophilia A and B, respectively. Twelve products (35%) used model‐based approaches (population PK/PD and exposure‐response). Over the past 5 years (2013 to 2017), there is a trend for increased application of MIDD approaches as compared to the previous cohort years (2008 to 2012). Conclusion: In conclusion, clinical pharmacology has played a major role in regulatory review of plasma‐derived products, and we expect that the application of quantitative methods will further evolve for these products under the FDA MIDD programme.